Psychosomatic respond as a challenge while working with combatants - Sobolta Юлія (Psychosomatic Medicine and General Practice, 2020)
The article reveals in retrospect the issues of psychological trauma and somatization among combatants. Literature review and available data analysis demonstrate the significance of the problem and field for further researches. Hereafter specified psychosomatic aspects of the homecoming of combatants; either analyzed the Ukrainian statistics of stress-related disorders. Outlined understanding of psychosomatization in nowadays psychological knowledge and its place between the issues of homecoming. The hypotheses put forward related to steps called for the reduction of the psychosomatization among the particular cohort.